2021
DOI: 10.1093/infdis/jiab322
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of Acute Respiratory Illness Associated With Human Adenovirus Type 4 at the United States Coast Guard Academy, 2019

Abstract: Background Although a human adenovirus (HAdV) vaccine is available for military use, officers-in-training are not routinely vaccinated. We describe an HAdV-associated respiratory outbreak among unvaccinated cadets at the U.S. Coast Guard Academy and its impact on cadet training. Methods We defined a case as a cadet with new onset cough or sore throat during August 1–October 4, 2019. We reviewed medical records and distributed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…The only difference is position 19555 A/G, corresponding to hexon I461V. The subclade of isolate 21947 and five other isolates shares almost identical sequence with viruses that caused outbreaks in US Naval Academy in 2016 (MG030483) and US Coast Guard in 2019 (MT771648) (4, 8). One unique finding in this study is a novel 18 nucleotides long deletion presents in the 3’-terminal inverted terminal repeat (ITR) at position 35927 of HAdV4 isolate 21984_S4TF75 (OM649206), while the 5’-terminal ITR remains unchanged.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…The only difference is position 19555 A/G, corresponding to hexon I461V. The subclade of isolate 21947 and five other isolates shares almost identical sequence with viruses that caused outbreaks in US Naval Academy in 2016 (MG030483) and US Coast Guard in 2019 (MT771648) (4, 8). One unique finding in this study is a novel 18 nucleotides long deletion presents in the 3’-terminal inverted terminal repeat (ITR) at position 35927 of HAdV4 isolate 21984_S4TF75 (OM649206), while the 5’-terminal ITR remains unchanged.…”
Section: Resultsmentioning
confidence: 98%
“…HAdV types 4, 7 and 14 were reported causing ARI in the military (4, 8, 17). This study identified these three adenoviruses in one season, 2018 - 2019.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations